BN Embedded Polycyclic π-Conjugated Systems: Synthesis, Optoelectronic Properties, and Photovoltaic Applications - Huang, Jianhua; Li, Yuqing (Frontiers in Chemistry, 2018)
In the periodic table of elements, boron (B, atomic number, 5) and nitrogen (N, atomic number 7) are neighboring to the carbon (C, atomic number 6). Thus, the total electronic number of two carbons (12) is equal to the electronic sum of one boron (5) and one nitrogen (7). Accordingly, replacing two carbons with one boron and one nitrogen in a π-conjugated structure gives an isoelectronic system, i.e., the BN perturbed π-conjugated system, comparing to their all-carbon analogues. The BN embedded π-conjugated systems have unique properties, e.g., optical absorption, emission, energy levels, bandgaps, and packing order in contrast to their all-carbon analogues and have been intensively studied in terms of novel synthesis, photophysical characterizations, and electronic applications in recent years. In this review, we try to summarize the synthesis methods, optoelectronic properties and progress in organic photovoltaic (OPV) applications of the representative BN embedded polycyclic π-conjugated systems. Firstly, the narrative will be commenced with a general introduction to the BN units, i.e., B←N coordination bond, B-N covalent bond, and N-B←N group. Then, the representative synthesis strategies toward π-conjugated systems containing B←N coordination bond, B-N covalent bond, and N-B←N group will be summarized. Afterwards, the frontier orbital energy levels, optical absorption, packing order in solid state, charge transportation ability and photovoltaic performances of typical BN embedded π-conjugated systems will be discussed. Finally, a prospect will be proposed on the OPV materials of BN doped π-conjugated systems, especially their potential applications to the small molecules organic solar cells.